The Effect of Herbicides and Cultivation Systems on Rice (Oryza sativa L.) Yield - Umiyati, Uum; Widayat, Dedi; Natasya, Kezia Putri (Jurnal Perlindungan Tanaman Indonesia, 2023)
The rice cultivation systems commonly used by farmers are the transplanted (called ‘Tapin’) and the direct-seeded (called ‘Tabela’) system. The Tabela system has many advantages over the Tapin system but has a weakness: the increase in weed population due to water conditions during transplantation. Therefore, weed management is necessary to increase rice yields. One way to control weeds is by applying herbicides. Using a single active ingredient herbicide continuously increases the chances for weeds to develop resistance against these active ingredients. Therefore, mixing herbicides with different active ingredients can be an alternative to improve weed management. This study aims to determine the effect of weed control and cropping systems to suppress weeds and provide the highest growth and rice yield. The research was conducted at the Agricultural Training and Development Research Center (Sanggar Penelitian Latihan dan Pengembangan Pertanian [SPLPP]) of the Faculty of Agriculture, Universitas Padjadjaran, Ciparay, Bandung Regency. This research was designed as a separate plot design with ten treatments and three replications with the main plot of cropping system and subplots of weed control. Weed management treatments consisted of bensulfuron-methyl 12% and bispyribac-sodium 18%; penoxsulam 15 g/L and pretilachlor 385 g/L; cyhalofop-butyl 100 g/L; manual weeding; and untreated control. Results that showed significant differences were tested using Duncan's test (DMRT) with α = 5%. Results showed that the Tabela system combined with bensulfuron-methyl 12% and bispyribac-sodium 18% suppressed weed growth and provided good growth and rice yield.